Towards microstructure-based analysis and design for seepage water in underground engineering: Effect of image characteristics. (November 2019) - Hu, Yong; Li, Yun An; Lin, Jun Lin; Ruan, Cheng Ke; Chen, Shu Jian; Tang, Hui Ming; Duan, Wen Hui
Highlights: Microstructure based properties prediction for numerical simulation of seepage water. Quantification of image characteristics for seepage related properties. State of the art high-resolution BSE imaging of pores structures in silty clay with very high signal to noise ratio. High-resolution planar Lattice Boltzmann flow simulation. Recommendations for future image acquisition. Abstract: Numerical modelling has been one of the most effective approaches for predicting seepage in tunnelling and underground projects. However, the applicability of such numerical simulation heavily relies on the information available for the properties of earth materials on site. Therefore, earth material property predictions based on imaging their microstructure has become a widely interested field. Despite the board use of various advanced imaging techniques to obtain information about the microstructure, there is still a lack of knowledge on the effect of image characteristics. By using high-resolution 2D Lattice Boltzmann method flow simulations, this paper quantified the impact of different image characteristics on the seepage-related property of silty clay. In order to guide future numerical simulations of seepage in tunnelling and underground construction, recommendations were given for proper image requisition in the microstructure-based analysis.